Digital Sphygmomanometer Detects Systole Diastolic Display - Aulia, Farahun Nisa; Pudji, Andjar; Sumber, Sumber; Ullah, Naqeeb (Jurnal Teknokes, 2023)
Hypertension. characterized by elevated blood pressure against artery walls. can be influenced by a patient's body temperature. Therefore. detecting body temperature before measuring blood pressure is essential for accurate assessment. Currently. Digital Tension and Body Temperature parameters are typically evaluated separately. To address this. we propose a novel approach to combine these parameters into a single unit. enhancing health monitoring. Utilizing MPX5050GP for blood pressure and MLX90614 for body temperature detection. Both sensors are directly connected to the Arduino UNO microcontroller. enabling seamless data processing and display on the Nextion LCD. Experimental results demonstrate the device's effectiveness. with systolic blood pressure measurements showing a Maximum error: 2.23%. minimum error: 0.53% for systolic measurements. Diastolic measurements have with a remarkable maximum error of only 4.69% and a minimal error of 1.79%. Additionally. the body temperature measurements exhibited a Achieved exceptional precision with errors as low as 0.45% and a maximum of 1.65%. Successfully completed. this design facilitates simultaneous measurement of two vital parameters. Its potential to streamline health monitoring could significantly impact hypertension management and other related conditions. Further validation and implementation in clinical settings are anticipated to enhance its utility and benefits.